Magnetic resonance neurography: improved diagnosis of peripheral neuropathies - Hayes, Jennifer; Bendszus, Martin (Neurotherapeutics, 2021)
Peripheral neuropathies account for the most frequent disorders seen by neurologists, and causes are manifold. The traditional diagnostic gold-standard consists of clinical neurologic examinations supplemented by nerve conduction studies. Due to well-known limitations of standard diagnostics and atypical clinical presentations, establishing the correct diagnosis can be challenging but is critical for appropriate therapies. Magnetic resonance neurography (MRN) is a relatively novel technique that was developed for the high-resolution imaging of the peripheral nervous system. In focal neuropathies, whether traumatic or due to nerve entrapment, MRN has improved the diagnostic accuracy by directly visualizing underlying nerve lesions and providing information on the exact lesion localization, extension, and spatial distribution, thereby assisting surgical planning. Notably, the differentiation between distally located, complete cross-sectional nerve lesions, and more proximally located lesions involving only certain fascicles within a nerve can hold difficulties that MRN can overcome, when basic technical requirements to achieve sufficient spatial resolution are implemented. Typical MRN-specific pitfalls are essential to understand in order to prevent overdiagnosing neuropathies. Heavily T2-weighted sequences with fat saturation are the most established sequences for MRN. Newer techniques, such as T2-relaxometry, magnetization transfer contrast imaging, and diffusion tensor imaging, allow the quantification of nerve lesions and have become increasingly important, especially when evaluating diffuse, non-focal neuropathies. Innovative studies in hereditary, metabolic or inflammatory polyneuropathies, and motor neuron diseases have contributed to a better understanding of the underlying pathomechanism. New imaging biomarkers might be used for an earlier diagnosis and monitoring of structural nerve injury under causative treatments in the future.
Gesehen am 03.05.2023